Suction Curettage and Foley Balloon as a First-Line Treatment Option for Caesarean Scar Pregnancy and Reproductive Outcomes - Aslan, Melike; Yavuzkir, Seyda (Dove Medical Press Ltd, 2021)
Background: Caesarean scar pregnancy (CSP) is associated with various serious pregnancy complications. This study presents the outcomes of patients treated with suction curettage and Foley balloon as the first-line treatment for CSP as well as their future outcomes in terms of successful pregnancy. Methods: Of the 44 patients diagnosed with CSP between January 2015 and April 2019, 42 who provided consent for the termination of pregnancy and who simultaneously underwent the transabdominal ultrasound-guided suction curettage + Foley balloon treatment were included in the study. These patients were then contacted and interviewed to collect data concerning their post-treatment number of pregnancies, number of miscarriages, number of live or dead births, mode of delivery, delivery time as well as whether any abnormal placental invasion or uterine ruptures developed. Results: Transabdominal ultrasound-guided suction curettage + Foley balloon was simultaneously performed as the first-line treatment in 42 patients with CSP. In two of these cases, wherein post-treatment level of beta-hCG reached a plateau, single-dose systemic methotrexate was administered. Emergency surgical intervention, hysterectomy, massive blood transfusion and additional systemic methotrexate administration were not required. Twenty-six of 42 patients could be contacted. 18/26 were trying to conceive. 6/18 patients had secondary infertility, and 12/18 patients managed to conceive. 8/12 had caesarean delivery at full term. 1/12 was 16-week pregnant, 1/12 had tubal ectopic pregnancy and 2/12 had first-trimester abortus. Conclusion: When administered as the first-line treatment for CSP, the suction curettage + Foley balloon treatment is a highly successful, cheap and easily performed minimally invasive method that requires only a short hospital stay, making it comfortable for patients. Compared with other uterine-sparing methods, it does not harm fertility and has positive effects on patients' future fertility outcomes.
Keywords: caesarean scar ectopics; first-line management; suction curettage; Foley balloon; pregnancy outcomes